Determination of common triterpenoids and phytosterols in vegetable waxes by HPTLC—densitometry and HPTLC—image analysis. Issue 5 (2nd April 2016) - Martelanc, Mitja; Naumoska, Katerina; Vovk, Irena
ABSTRACT: Screening of triterpenoids and phytosterols in unhydrolyzed and hydrolyzed cuticular waxes of zucchini, eggplant, tomato, red pepper, mangold, spinach, lettuce, white-colored radicchio di Castelfranco, radicchio Leonardo, white cabbage, red cabbage, and Savoy cabbage was performed on high-performance thin-layer chromatographic (HPTLC) silica gel 60 and C18 RP plates developed in n -hexane-ethyl acetate (5:1, v / v ) and ethyl acetate-acetonitrile (3:2, v / v ), respectively. Postchromatographic derivatization by anisaldehyde detection reagent enabled densitometry at 535 nm and image analysis at 366 nm and white light. Semi-quantitative analysis on the silica gel plates using lupeol standard confirmed that the studied vegetables contain up to 1.5 mg of total triterpenols per 100 g, which classify them as important sources of triterpenols in human diet. Quantification of lupeol in waxes of nine white cabbage varieties on HPTLC C18 RP plates was achieved using densitometry and image analysis, which produced comparable results. Different amounts of lupeol were observed between the investigated white cabbage varieties. A comparison between unhydrolyzed and hydrolyzed cuticular waxes by HPTLC C18 RP—image analysis suggested the presence of conjugated triterpenoids and phytosterols in vegetable cuticular waxes.